The interaction of neonatal abstinence syndrome and opioid use disorder treatment availability for women insured by medicaid. Issue 1 (6th October 2020) - Reising, Virginia A.; Horne, Ashley; Bennett, Amanda C.
Abstract: Objective: This paper will discuss the process of mapping opioid use disorder (OUD) treatment resources for pregnant women and discuss the intersection between treatment resources and rates of neonatal abstinence syndrome (NAS). Design: A resource manual was developed through a systematic process with stakeholders across Illinois. Resources were mapped by county and overlaid with county rates of NAS, using hospital discharge data. Results: Across Illinois, 89 treatment resources were identified for pregnant women insured by Medicaid. Resources were concentrated in 36% of Illinois' counties. Counties with limited treatment resources generally had high rates of NAS. Sixty‐six percent of NAS cases among rural Illinois residents had no OUD treatment resources in their county. Rural counties had less access to medication‐assisted treatment (MAT), the standard of care for treatment of OUD, compared with other counties across the state. Conclusions: Efforts to increase OUD treatment options for pregnant women insured by Medicaid should concentrate on geographic areas with limited access and high need.